Development of interprofessional case discussion series from an interprofessional geriatrics clinic and its influence on professional identity formation. (6th December 2021) - Halli‐Tierney, Anne D.; McKinney, Robert E.; Gold, Allyson E.; Allen, Rebecca S.; Carroll, Dana G.
Abstract: This article focuses on the use of interprofessional case discussions as an interactive learning approach to cultivate professional identity formation among multiple professions while simultaneously promoting geriatric education and enhancing learning about diverse disciplines needed for care of the older adult.